Islamic Law Values Transformation in the Reconstruction of the Legality Principle of Indonesian Criminal Code - Sri Endah Wahyuningsih (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
Criminal code of Indonesia is still using Dutch colonoal era with background values of individualistic and liberalistic, so it is not in accordance with the conditions—in which we had already been recognized as an independent nation. Therefore it is necessary to make reconstruction penal code with tranformation of the values of Islamic law, because the sociological, political and philosophical position of Islamic law occupies an important position as a source of law. Policy transformation is done by formulating the universal values of Islamic law into the process of formulation of the principle of legality in criminal code of Indonesia, because the principle of legality in criminal code currently recognizes only source legal written (Act) as a legal basis to convict, and does not recognize the law source who live in the community (common law) as the legal basis to convict. As a result, enforcement of criminal law in Indonesia unfairly perceived by the public as many deeds by people regarded as disgraceful act but the offender can not subjected of criminal sanctions because of his actions not constitute a crime under the Criminal Code. Keywords: Islamic law, legality principles, Criminal Code